Analisis Penggunaan Kayu Bakar pada Proses Pembuatan Gula Merah (Arenga pinnata. Merr) oleh Kelompok Tani Buttu Puang - Hardianti, Ayu; Idris, Andi Irmayanti (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2021)
Wood is a substitute energy resource for fossil fuels. This energy source is widely used for household and industrial purposes. The purpose of this study was to determine the amount of use of firewood in the manufacture of palm sugar (Arenga pinnata Merr.) by Buttu Puang Farmer’s Group. This research was conducted in Tappina Hamlet, Mirring Village, Binuang District with 9 respondents. The data was collected by weighing the firewood before and after the cooking of the palm sap based on the grouping of the wood species and the density test. The dominant types of firewood used are white teak (Gmelina arborea.Roxb), local teak (Tectona grandis.Linn), gamal (Gliricidia sepium), mountain fir (Casuarina junghulniana Miq) and right-wing tree (Canangium odoratum). The type of wood that has a low density value is jabon wood (Anthocephalus cadamba Miq) 0.49 gr/cm and the type of wood with a high density value is Kananga wood (Canangium odoratum) 0.96 gr/cm. The amount of use of firewood in one brown sugar production is 0.68 m3/unit/day, per months is 20.52 m³/unit/month, in one year is 143.64 m³/unit/year. The average use of firewood is 0.08 m3/unit/day, in one month is 2.28 m3/unit/month and the average use in one year of palm sap productivity is 15.96 m³/unit/year.